EFEKTIVITAS PEMBELAJARAN JARAK JAUH DALAM PEMBELAJARAN PJOK BERBASIS DARING UNTUK PESERTA DIDIK KELAS X DI SMA NEGERI 1 BANGLI TAHUN PELAJARAN 2021/2022 - I Gede Eka Kurnia Wiratama; I Gede Suwiwa; Ni Putu Dwi Sucita Dartini (Jurnal IKA, 2022)
This study aims to determine the effectiveness of distance learning in online-based PJOK learning for class X students at SMA Negeri 1 Bangli for the academic year 2021/2022. The approach used in this research is a descriptive approach with a qualitative phenomenological type of research. The population of this study were students of class X SMA N 1 Bangli with a total of 281 people. The sampling technique of this study used Isaac and Michael's table with an error rate of 5% so that the number of samples in this study was 155 students of class X, and 1 teacher of PJOK class X at SMA Negeri 1 Bangli.. The validity of the data in this study was determined by using credibility, transferability, dependability, and confirmability. The results showed that distance learning in online-based PJOK learning at SMA Negeri 1 Bangli was declared less effective, due to several reasons, namely: (1) online learning complicates the learning process carried out by students, (2) face-to-face learning is more fun than learning online, (3) there are obstacles such as limited internet networks, study quotas, and sometimes difficult applications to access. (4) learning objectives that are not achieved. So it can be concluded that distance learning in online PJOK learning is less effective in implementing PJOK learning at SMA Negeri 1 Bangli